The C-terminal selenenylsulfide of extracellular/non-reduced thioredoxin reductase endows this protein with selectivity to small-molecule electrophilic reagents under oxidative conditions - Qin, Huijun; Guo, Chenchen; Chen, Bozhen; Huang, Hui; Tian, Yaping; Zhong, Liangwei (Frontiers in Molecular Biosciences, 2024)
Mammalian cytosolic thioredoxin reductase (TrxR1) serves as an antioxidant protein by transferring electrons from NADPH to various substrates. The action of TrxR1 is achieved via reversible changes between NADPH-reduced and non-reduced forms, which involves C-terminal selenolthiol/selenenylsulfide exchanges. TrxR1 may be released into extracellular environment, where TrxR1 is present mainly in the non-reduced form with active-site disulfide and selenenylsulfide bonds. The relationships between extracellular TrxR1 and tumor metastasis or cellular signaling have been discovered, but there are few reports on small-molecule compounds in targeted the non-reduced form of TrxR1. Using eight types of small-molecule thiol-reactive reagents as electrophilic models, we report that the selenenylsulfide bond in the non-reduced form of TrxR1 functions as a selector for the thiol-reactive reagents at pH 7.5. The non-reduced form of TrxR1 is resistant to hydrogen peroxide/oxidized glutathione, but is sensitive to certain electrophilic reagents in different ways. With 5,5′-dithiobis-(2-nitrobenzoic acid) (DTNB) and S-nitrosoglutathione (GSNO), the polarized selenenylsulfide bond breaks, and selenolate anion donates electron to the dynamic covalent bond in DTNB or GSNO, forming TNB-S-Se-TrxR1 complex or ON-Se-TrxR1 complex. The both complexes lose the ability to transfer electrons from NADPH to substrate. For diamide, the non-reduced TrxR1 actually prevents irreversible damage by this oxidant. This is consistent with the regained activity of TrxR1 through removal of diamide via dialysis. Diamide shows effective in the presence of human cytosolic thioredoxin (hTrx1), Cys residue(s) of which is/are preferentially affected by diamide to yield disulfide, hTrx1 dimer and the mixed disulfide between TrxR1-Cys497/Sec498 and hTrx1-Cys73. In human serum samples, the non-reduced form of TrxR1 exists as dithiothreitol-reducible polymer/complexes, which might protect the non-reduced TrxR1 from inactivation by certain electrophilic reagents under oxidative conditions, because cleavage of these disulfides can lead to regain the activity of TrxR1. The details of the selective response of the selenenylsulfide bond to electrophilic reagents may provide new information for designing novel small-molecule inhibitors (drugs) in targeted extracellular/non-reduced TrxR1.